Prevalence and risk factors of portal vein thrombosis following hepatectomy: a systematic review and meta‑analysis - Yang Qun; Feng Meiying; Yao Weiming; He Dan (Videosurgery and Other Miniinvasive Techniques)
Introduction: The prevalence and risk factors of portal vein thrombosis (PVT) are largely unclear, with an increasing number of studies reporting inconsistent results. Aim: The current study aimed to evaluate the prevalence and risk factors of PVT following hepatectomy through a systematic review and meta‑analysis. Materials and methods: A comprehensive literature search was conducted across multiple databases (PubMed, Embase, and the Cochrane Library) to identify relevant studies. Prospective and retrospective studies reporting on PVT following hepatectomy were included. The Newcastle ‑Ottawa Scale (NOS) was used to assess study quality, and the random effects model was used to analyze the prevalence and risk factors. Results: A total of 15 studies involving 5145 patients were included in the current meta‑analysis. The pooled prevalence of PVT following hepatectomy was 9% (95% CI, 7%–12%) with substantial heterogeneity (I2 = 93.1%). Subgroup analyses showed that a prospective design and larger sample size were associated with lower prevalence rates. PVT prevalence was higher among the patients undergoing simultaneous splenectomy and hepatectomy. Liver cirrhosis (odds ratio [OR], 5.18; 95% CI, 1.85–14.47), portal vein resection (OR, 5.07; 95% CI, 2.2–11.66), and right ‑sided hepatectomy (OR, 6.26; 95% CI, 1.8–21.76) were significant risk factors for PVT. Conlusions: PVT is a notable complication following hepatectomy, with an overall prevalence of 9%. Specific factors that significantly increase the risk of PVT include liver cirrhosis, portal vein resection, and right‑sided hepatectomy.